1992
DOI: 10.1093/ajcn/55.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Plasma β-carotene response in humans after meals supplemented with dietary pectin

Abstract: The purpose of this study was to determine the effect of pectin on plasma response to beta-carotene in humans. Using a crossover design, we evaluated the effect on plasma beta-carotene in seven subjects when 12 g citrus pectin was added to a 2092 kJ (500 kcal) controlled meal with 25 mg beta-carotene. Plasma samples were collected at 0, 8, 30, 48, and 192 h after the meals. Plasma beta-carotene was quantified with the use of HPLC. The increase in plasma beta-carotene concentration was significantly reduced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
1
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(111 citation statements)
references
References 15 publications
8
96
1
6
Order By: Relevance
“…Pectin from fruit matrices has been suggested to interfere with micelle formation by partitioning bile salts and fat in the pectin gel phase (Palafox-Carlos, Ayala-Zavala, & Gonzalez-Aguilar, 2011;Parada & Aguilera, 2007;Rock & Swendseid, 1992) that is necessary for the absorption of lipophilic carotenoids.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Pectin from fruit matrices has been suggested to interfere with micelle formation by partitioning bile salts and fat in the pectin gel phase (Palafox-Carlos, Ayala-Zavala, & Gonzalez-Aguilar, 2011;Parada & Aguilera, 2007;Rock & Swendseid, 1992) that is necessary for the absorption of lipophilic carotenoids.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Epidemiological studies have shown an inverse correlation between consumption of carotenoid-rich fruits and vegetables, and the incidence of cancers of the gastrointestinal tract (Kant, Block, Schatzkin, & Nestle, 1992;Kiokias & Gordon, 2004;Mayne, 1996;Rock & Swendseid, 1992), cardiovascular diseases (Krinsky, 1998;Murr et al, 2009), diabetes (Yeum & Russell, 2002), some inflammatory diseases (Perera & Yen, 2007), as well as age-related macular degeneration (Snodderly, 1995). The most documented function of β-carotene is its provitamin A activity, with consequent health benefits, such as maintenance of epithelial function, embryonic development, and immune system function (Diplock, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Food fibers reduce the bioavailability of carotenoids by trapping them, or by interacting with biliary acids having as result increase in the fecal excretion of lipids and fat-soluble substances like carotenoids [28]. Therefore, the low consumption of fibers by these women could be beneficial for their pro-Vitamin A absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados obtidos por estudo realizado por Rock & Swendseid 33 indicaram um efeito inibitório da pectina, o que poderia justificar os reduzidos níveis plasmáticos de β-caroteno em humanos após a ingestão de alimentos ricos em carotenóides, quando comparados a doses equivalentes de suplementos de β-caroteno.…”
Section: Fatores Influentes (Slamenghi)unclassified